Genetic Analysis of Quantitative Traits Associated with Drought Tolerance Attributes in Rice RIL Populations Under Reproductive Moisture Stress (Journal of Pharmaceutical Negative Results, 2022)
Rice productivity and yield stability are negatively affected by moisture stress, becoming a challenge to farming systems as the world's climate shifts. Drought is one of the primary factors limiting rice production in rainfed ecosystems during the reproductive phase. In the context of abiotic stress breeding, the finding of drought tolerant genotypes during the reproductive stage provides researchers with extra benefits in developing stable varieties for moisture stress. Two different parents, CT- 9993 and Samba Mashuri were utilized to develop recombinant inbred lines for evaluation of drought tolerance during the study. Findings of the study expressed that yield and yield-attributing parameters varied significantly for genetic correlation, heritability, genetic advancement, etc. among RILs and parental lines over stressed experiment. Result of genetic analysis identified several lines which can be further exploited in developing drought tolerant cultivars to get sustainable yield under reproductive stress condition in rice.